2022
DOI: 10.1111/jfbc.14039
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of whey protein concentrate on SARS‐CoV‐2‐targeted furin activity and spike protein‐ACE2 binding in methotrexate‐induced lung damage

Abstract: This study aims to investigate the effects of whey proteins on SARS CoV‐2 in methotrexate‐induced lung tissue damage in rats. To determine the possible effects, rats were divided into four groups as control, control + whey, methotrexate (20 mg/kg, i.p.) and methotrexate + whey. Whey protein concentrate (2 g/kg, oral gavage) was administered for 10 days. Cytokine levels were measured and protein electrophoresis was carried out in serum samples. Lipid peroxidation, nitric oxide and glutathione level, and superox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Enhancing GSH, mainly through NAC, GSH precursors or pro-GSH compound administration, becomes a potential treatment option for SARS-CoV-2 infection and COVID-19 disease by reducing oxidative stress and cytokine expression especially in diabetic patients at risk of more severe disease ( Singh et al, 2022 ). Whey protein concentrate ameliorates lung damage and inhibits lung furin activity targeting SARS-CoV-2 S1/S2 site cleavage and SARS CoV-2 spike protein-angiotensin converting enzyme binding and could be used to protect against COVID-19 inhibiting SARS-CoV-2 cell entry ( Tufan et al, 2022 ). A combination of vitamin D and L-cysteine administration significantly augmented GSH levels and lowered oxidative stress and inflammation ( Jain et al, 2018 ; Jain and Parsanathan, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing GSH, mainly through NAC, GSH precursors or pro-GSH compound administration, becomes a potential treatment option for SARS-CoV-2 infection and COVID-19 disease by reducing oxidative stress and cytokine expression especially in diabetic patients at risk of more severe disease ( Singh et al, 2022 ). Whey protein concentrate ameliorates lung damage and inhibits lung furin activity targeting SARS-CoV-2 S1/S2 site cleavage and SARS CoV-2 spike protein-angiotensin converting enzyme binding and could be used to protect against COVID-19 inhibiting SARS-CoV-2 cell entry ( Tufan et al, 2022 ). A combination of vitamin D and L-cysteine administration significantly augmented GSH levels and lowered oxidative stress and inflammation ( Jain et al, 2018 ; Jain and Parsanathan, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whey peptides (4–13 residues) isolated from buffalo milk and colostrum have also been reported to show antiviral activity against SARS‐CoV‐2 in various ways, that is, inhibiting replication transcription complex, virion assembly, and endosomal maturation in addition to blocking viral entrance by binding to spike S and ACE2 (Pradeep et al, 2021 ). Recently Tufan et al ( 2022 ) reported that administration of WPC at the dose rate of 2 g/kg for 10 days reduced the oxidative lung injury caused by methotrexate and prevented lung furin activity and the binding of SARS‐CoV‐2 spike protein to ACE2 receptors. Different whey‐derived peptides, that is, “IPP,” “IIAE,” “LIVTQ,” and “LVYPFP,” may inhibit SARS‐CoV‐2 entrance by suppressing ACE2 through precise molecular interactions with important ACE2 residues (Chamata et al, 2021 ).…”
Section: Milk Proteinsmentioning
confidence: 99%
“…GSH dysregulation might cause global immune cell autophagy decline with increased generation of proinflammatory cytokines in aging, further provoked by mitochondrial ROS signaling (293). Whey protein concentrate ameliorates lung damage and inhibits lung furin activity targeting SARS-CoV-2 S1/S2 site cleavage and SARS CoV-2 spike protein-angiotensin converting enzyme binding and could be used to protect against COVID-19 inhibiting SARS-CoV-2 cell entry (300). Glutamine, glycine, N-acetylcysteine, selenium, whey protein isolates with bonded cysteine, GSH and pro-GSH supplementation improves GSH deficiency, oxidative stress, mitochondrial dysfunction, inflammation, insulin resistance, endothelial dysfunction, genotoxicity, muscle strength, cognition and surfactant regeneration (301)(302)(303)(304)(305)(306)(307).…”
Section: Summary and Conclusion: Glutathione And Early (Premature) In...mentioning
confidence: 99%